PHOTOMETRY AND BLAZHKO EFFECT IN RR LYR-TYPE STAR AE LEO - Udovichenko, S. N.; Keir, L. E. (Одеські астрономічні публікації, 2017)
The photometric observations for the RR Lyr-type star AE Leo in the Astronomical station near Odessa using the 48-cm reﬂector AZT-3 and the CCD photometer equipped with the V ﬁlter have been carried out. The light curves shows variable amplitude of light maxima and the moderate Blazhko eﬀect. The analysis of the O-C light maxima for our observations and the ASAS, NSVS data indicates the secular period changes.